2005 European Conference on Power Electronics and Applications 2005
DOI: 10.1109/epe.2005.219271
|View full text |Cite
|
Sign up to set email alerts
|

Paralleling of low-voltage MOSFETs operating in avalanche conditions

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In the case of avalanche simulation, the model has to include electro-thermal coupling, as the drain-to-source voltage is mainly related to the transistor temperature and to the drain current. This is not obvious in a single-transistor per switch setup (as in the converter described in this paper), but is very important when paralleling devices [23], because it has a strong effect on current sharing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of avalanche simulation, the model has to include electro-thermal coupling, as the drain-to-source voltage is mainly related to the transistor temperature and to the drain current. This is not obvious in a single-transistor per switch setup (as in the converter described in this paper), but is very important when paralleling devices [23], because it has a strong effect on current sharing.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in [14] that is not only temperature-dependent, but also strongly related to the drain current. A specific resistance of the avalanche path, several times higher than the has a strong influence on the breakdown voltage.…”
Section: Capacitancesmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig.1.7, where the red squares refer to the failed components, and the green squares refer to different stressors. It is concluded that the IGBT and chip resistors are critical components according to these specific different research activity in the literature [45], [46], [47], [48], [49], [20], [50], [42], [51], [40], [52], [53], [26], [54], [55], [56], [57], [39], [58], [59], [60], [61], [62], [63] and [64]. It can be concluded from this figure that the thermal cycles are a very common source of failure in the power electronics of the electro-mobile applications.…”
Section: Component Failures In Power Electronics In Electro Mobility mentioning
confidence: 99%
“…Based on the turn-on mechanism of the power MOSFET [15], [16], the dynamic modeling for a Fuji 2SK3677-01MR power MOSFET is illustrated in Fig. 1.…”
Section: Mosfet and Circuit System Modelingmentioning
confidence: 99%